2022
DOI: 10.1029/2021gl096270
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged and Pervasive Perturbations in the Composition of the Southern Hemisphere Midlatitude Lower Stratosphere From the Australian New Year's Fires

Abstract: Intense heating by severe wildfires can trigger vigorous smoke-infused thunderstorms, termed pyrocumulonimbus (pyroCbs), that rapidly loft polluted air from the surface to the lower stratosphere (e.g., Fromm et al., 2010;Peterson et al., 2021). The Aura Microwave Limb Sounder (MLS) provides profiles of a suite of atmospheric trace gases, including ozone, water vapor, reservoir and reactive chlorine species, and several markers of biomass burning pollution. Although MLS had observed significant composition anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 49 publications
9
43
0
Order By: Relevance
“…By October Cl y partitioning is within the range of previous years. Similar findings reported by Santee et al (2022) and Bernath et al (2022).…”
Section: Observations Of Aerosol Extinction Chlorine and Nitrogen Spe...supporting
confidence: 91%
See 2 more Smart Citations
“…By October Cl y partitioning is within the range of previous years. Similar findings reported by Santee et al (2022) and Bernath et al (2022).…”
Section: Observations Of Aerosol Extinction Chlorine and Nitrogen Spe...supporting
confidence: 91%
“…Santee et al. (2022) suggest that the enhancements in MLS 100 hPa water vapor (Figure 1f) may be attributable to the wet phase of the tropical tape recorder. They showed that 2020 MLS SH midlatitude LS water (∼4 ppm) and MERRA2 temperature (212–224 K) were within the 2005–2019 data envelope.…”
Section: Observations Of Aerosol Extinction Chlorine and Nitrogen Spe...mentioning
confidence: 94%
See 1 more Smart Citation
“…Solomon et al (2022) show evidence for mid-latitude chemistry driving large observed nitrogen oxide changes following the fires. Santee et al (2022) and Bernath et al (2022) show remarkable changes in hydrochloric acid and chlorine nitrate at mid-latitudes after the Australian fires, but the chemical mechanism causing those changes has not yet been identified, nor has a clear link to polar chemistry been established. Wildfire soot may also contribute to dynamical changes in the strength of the vortex through changes in radiative heating, but this mechanism has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Santee et al. (2022) and Bernath et al. (2022) show remarkable changes in hydrochloric acid and chlorine nitrate at mid‐latitudes after the Australian fires, but the chemical mechanism causing those changes has not yet been identified, nor has a clear link to polar chemistry been established.…”
Section: Discussionmentioning
confidence: 99%